2021
DOI: 10.1016/j.hlc.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

An Hypothesis: Disproportion Between Cardiac Troponin and B-Type Natriuretic Peptide Levels—A High Risk and Poor Prognostic Biomarker in Patients With Fulminant Myocarditis?

Abstract: In our clinical practice, we recently found some patients with severe fulminant myocarditis (FM) who showed persistently elevated cardiac troponin (cTn) levels and "seemingly normal" B-type natriuretic peptide (BNP) level, and who subsequently progressed to poor outcomes. Indeed, this sounds contrary to conventional wisdom, but it is not an accidental phenomenon. Fulminant myocarditis is a rapidly progressive disease associated with high mortality. Recent studies have shown that patients with FM are significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…According to the characteristics of troponins, the type of cardiac troponin I and T are the new isoforms that are present in adult cardiac tissues ( Yu et al, 2021 ). About 46–97% of patients with immune myocarditis have increased serum troponin levels ( Escudier et al, 2017 ; Mahmood et al, 2018 ; Mir et al, 2018 ; Awadalla et al, 2020 ; Finke et al, 2021 ).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the characteristics of troponins, the type of cardiac troponin I and T are the new isoforms that are present in adult cardiac tissues ( Yu et al, 2021 ). About 46–97% of patients with immune myocarditis have increased serum troponin levels ( Escudier et al, 2017 ; Mahmood et al, 2018 ; Mir et al, 2018 ; Awadalla et al, 2020 ; Finke et al, 2021 ).…”
Section: Diagnosismentioning
confidence: 99%
“…BNP is a specific biomarker reflecting the pressure or overload. BNP can indirectly tell us the function of the left ventricular (LV) strain in patients with heart failure or myocarditis ( Yu et al, 2021 ). All the pathogenesis which can lead to dysfunction of LV can also result in elevated BNP levels.…”
Section: Diagnosismentioning
confidence: 99%
“…hsTropT was correlated with cardiac structure and function to a greater extent than NT-proBNP. This may be explained by the findings of a previous study in which hsTropT was related to an abnormal myocardium, irrespective of causative factors, whereas NT-proBNP was mostly related to the compensatory cardiac ventricular response to pressure and volume overload [45] . In addition, a previous study showed that patients with high LVMI had low capillary density and high LV mass, which were related to microvascular dysfunction, resulting in an ischemic myocardium and the release of hsTropT [15] .…”
Section: Discussionmentioning
confidence: 93%
“…According to Xu et al LAd [OR: 1.226; 95% CI: 1.016–1.478; P = 0.034] and eGFR level [OR: 0.928; 95% CI: 0.87–0.989; P = 0.022] were predictors of FM ( 6 ). Besides, a combination of high cTn levels and low BNP levels, which suggested poor outcomes of the patient with FM ( 16 ). Liu et al found that the ACEF score, which was correlated with age, creatinine, and LVEF, [OR: 4.499; 95% CI: 0.960–1.061; p < 0.001] was a strong independent predictor of in-hospital mortality in children with FM, with an area under the ROC curve of.871 ( 7 ).…”
Section: Discussionmentioning
confidence: 99%